UPPER LITHOSPHERIC SEISMIC VELOCITY STRUCTURE ACROSS THE PRIPYAT TROUGH AND THE UKRAINIAN SHIELD ALONG THE EUROBRIDGE'97 PROFILE - Thybo H.; Knudsen M.E.; Sand R.; Janik T.; Guterch A.; Omelchenko V.D.; Kharitonov O.M.; Ilchenko T.; Lysynchuk D.V.; Skobelev V.M.; Grad M.; Garetsky R.G.; et al. (My University, 2003)
We present new results on the structure resulting from Palaeoproterozoic terrane accretion and later formation of one of the aulacogens in the East European Platform. Seismic data has been acquired along the 530-km-long, N-S-striking EUROBRIDGE'97 traverse across Sarmatia, a major crustal segment of the East European Craton. The profile extends across the Ukrainian Shield from the Devonian Pripyat Trough, across the Palaeoproterozoic Volyn Block and the Korosten Pluton, into the Archaean Podolian Block. Seismic waves from chemical explosions at 18 shot points at approximately 30-km intervals were recorded in two deployments by 120 mobile three-component seismographs at 3-4 kin nominal station spacing. The data has been interpreted by use of two-dimensional tomographic travel time inversion and ray trace modelling. The high data quality allows modelling of the P- and S-wave velocity structure along the profile. There are pronounced differences in seismic velocity structure of the crust and uppermost mantle between the three main tectonic provinces traversed by the profile: (i) the Pripyat Trough is a ca. 4-km-deep sedimentary basin, fully located in the Osnitsk-Mikashevichi Igneous Belt in the northern part of the profile. The velocity structure is typical for a Precambrian craton, but is underlain by a ca. 5-km-thick lowest crustal layer of high velocity. The development of the Pripyat Trough appears to have only affected the upper crust without noticeable thinning of the whole crust; this may be explained by a rheologically strong lithosphere at the time of formation of the trough. (ii) Very high seismic velocity and Vp/Vs ratio characterise the Volyn Block and Korosten Pluton to a depth of 15 km and probably also the lowest crust. The values are consistent with an intrusive body of mafic composition in the upper crust that formed from bimodal melts derived from the mantle and the lower crust. (iii) The Podolian Block is close to a typical cratonic velocity structure, although it is characterised by relatively low seismic velocity and Vp/Vs ratio. A pronounced SW-dipping mantle reflector from Moho to at least 70 kin depth may represent the Proterozoic suture between Sarmatia and Volgo-Uralia, the structure from terrane accretion, or a later shear zone in the upper mantle. The sub-Moho P-wave seismic velocity is high everywhere along the profile, with the exception of the area above the dipping reflector. This velocity change further supports a plate tectonic origin of the dipping mantle reflector. The profile demonstrates that structure from Palaeoproterozoic plate tectonic processes are still identifiable in the lithosphere, even where younger metamorphic equilibration of the crust has taken place. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Crustal accretion; Aulacogens; Secular lithospheric evolution; East European Craton; Seismic velocity; Ukrainian Shield